Corrosion by carbon and nitrogen metal dusting, carburisation and nitridation - Grabke, H. J.; Schütze, Michael (CRC ; Woodhead Pub., 2007)
This book reviews the factors affecting metal dusting and how it can be prevented in sectors such as the chemical and petrochemical industries and in the direct reduction of iron ores. It also considers the related corrosion phenomena of carburization and nitridation. Topics include: key processes involved in metal dusting; how this corrosion process affects a range of metals such as iron and steel, as well as nickel-based and chromium-based high-temperature alloys; effects of particular gas mixtures on the corrosion process and on the use of coatings to prevent metal dusting; processes involved in carburization and nitridation. -- Edited summary from book.
Keywords: Corrosion and anti-corrosives.; Case hardening.; Nitriding.; elektronické knihy; electronic books